THE POTENTIAL OF FAMILY PLANNING SERVICES IN ENHANCING THE UTILIZATION OF MODERN CONTRACEPTIVES: A CLUSTER ANALYSIS OF VILLAGE GROUPING IN WEST SULAWESI PROVINCE - Ashari Ramadhan; Arman, Andi Nur Zamzam (Badan Kependudukan Dan Keluarga Berencana Nasional, 2024)
Maternal and child mortality issue is a significant challenge in West Sulawesi, necessitating urgent intervention. The Maternal and Child Health (MCH) data for 2023 reveals maternal mortality at 48 and infant mortality at 359. The declining of 1.2% in modern contraceptive use to 51.14% in 2023 compared to the previous year, underscores the urgency for intervention. Meanwhile, each region exhibits distinct characteristics, conditions, and potentials to decide the right intervention for each region. The k-means algorithm in this research was used to perform regional clustering. The purpose of this study is to determine intervention strategies based on the conditions and potential of regional clusters. Cluster analysis highlights variations among clusters. Based on the analysis, clusters with unmet need below the expected target are clusters 1, 2, and 4. In determining intervention, the following aspects need to be considered specifically cluster 1 requires enhanced access to family planning services, cluster 2 needs improved dissemination of family planning information, while cluster 4 is characterized by high unmet needs and a lack of healthcare facilities, necessitates increased accessibility to family planning services and healthcare staff training. Customized strategies for each cluster are vital to optimize the utilization of resources effectively and efficiently